The impact of income diversification on the market value of Indonesian banking companies - Nasywa Ummi Syarifah; Achmad Nur Wahyu Kartiko; Windijarto Windijarto (Nur Science Institute, 2026)
This study examines the effect of bank income diversification on the market value of Indonesian banking firms. The sample consists of eight banks listed on the Indonesia Stock Exchange over the 2015 to 2021 period. Income diversification is measured by the proportion of Net Non-Interest Income (NNII), market value is proxied by Tobin’s Q, and bank profitability, measured by return on assets (ROA), is included as a control variable. The sample was selected purposively based on data availability and consistency, resulting in 56 observations. The study employs multiple linear regression analysis. The results indicate that income diversification has a positive and statistically significant effect on market value. These findings suggest that diversifying income sources can enhance bank valuation and encourage banks to expand non-interest income streams to sustain value creation. However, the study is limited by its sample size and observation period, which leaves room for broader future research. Theoretically, the findings support signaling theory and portfolio theory, which suggest that income diversification can serve as a positive signal to investors while reducing the risks associated with dependence on interest income. In practice, the study highlights the importance of income diversification strategies for improving market valuation and strengthening the competitiveness of Indonesian banks.